Is the brightness- contrast level of virtual reality videos significant for visually induced motion sickness? Experimental real-time biosensor and self-report analysis - Ugur, Emel; Konukseven, Bahriye Ozlem; Ergen, Mehmet; Aksoy, Mehmet Emin; Yoner, Serhat Ilgaz (Frontiers in Virtual Reality, 2024)
Background: Virtual reality is no longer created solely with design graphics. Real life 360° videos created with special shooting techniques are now offered as open access to users' experience. As a result, this widespread use of VR systems has increased the incidence of visually induced motion sickness.Objective: In the present study, we aimed to investigate impact of brightness-contrast levels of real-life 360° videos on susceptibility to visually induced motion sickness during immersive virtual reality headset viewing.In this study, 360° real-world day and night driving videos publicly available on YouTube VR were used as stimuli. Stimuli were presented in two-minute segments.Electrodermal activity was recorded throughout the stimulus presentation, and SSQ was administered immediately afterward.No significant difference was found between the experiments in terms of dermal activity. There is a statistically significant difference in total SSQ scores and in symptoms of fatigue, eye strain, head fullness, blurred vision, and dizziness (p < 0.005; p<0.01) after then the night video.The present study examined the likely impact of brightness and contrast levels in VR environments on VIMS provocation.